The Multiple Dimensions of Gender Stereotypes: A Current Look at Men’s and Women’s Characterizations of Others and Themselves - Hentschel, Tanja; Heilman, Madeline E.; Peus, Claudia V. (Frontiers in Psychology, 2019)
We used a multi-dimensional framework to assess current stereotypes of men and women. Specifically, we sought to determine (1) how men and women are characterized by male and female raters, (2) how men and women characterize themselves, and (3) the degree of convergence between self-characterizations and charcterizations of one’s gender group. In an experimental study, 628 U.S. male and female raters described men, women, or themselves on scales representing multiple dimensions of the two defining features of gender stereotypes, agency and communality: assertiveness, independence, instrumental competence, leadership competence (agency dimensions), and concern for others, sociability and emotional sensitivity (communality dimensions). Results indicated that stereotypes about communality persist and were equally prevalent for male and female raters, but agency characterizations were more complex. Male raters generally descibed women as being less agentic than men and as less agentic than female raters described them. However, female raters differentiated among agency dimensions and described women as less assertive than men but as equally independent and leadership competent. Gender stereotypes also were evident in self-ratings, with female raters rating themselves as less agentic than male raters and male raters rating themselves as less communal than female raters, although there were exceptions (e.g., no differences in independence and sociability self-ratings for men and women). Comparisons of self-ratings and ratings of men and women in general indicated that women tended to characterize themselves in more stereotypic terms – as less assertive and less competent in leadership – than they characterized others in their gender group. Men, in contrast, characterized themselves in less stereotypic terms – as more communal. Overall, our results show that a focus on facets of agency and communality can provide deeper insights about stereotype content than a focus on overall agency and communality.